1987
DOI: 10.2135/cropsci1987.0011183x002700060002x
|View full text |Cite
|
Sign up to set email alerts
|

Association of Alleles for High Stearic Acid with Agronomic Characters of Soybean1

Abstract: Alleles that control four to sevenfold increases in the content of stearic acid in soybean [Glycine max (L.) Merr.] oil have been obtained by artificial mutagenesis. The objective of this study was to evaluate the association of three alleles for high stearic acid with agronomic and chemical characters of soybean. Three mutant lines, A6 with 282 g kg−1 stearic acid, A9 with 163 g kg−1 stearic acid, and A10 with 146 g kg−1 stearic acid, each with a different allele at a single locus controlling stearic acid con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
2

Year Published

1991
1991
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 0 publications
1
30
2
Order By: Relevance
“…A6’s stearic acid phenotype was much lower in the three Missouri environments we studied (23.4 ± 4.4, 20.9 ± 2.9, and 22.3 ± 5.5%) as compared with the original report of 28.1% stearic acid (Hammond and Fehr 1983; Lundeen et al 1987), and this difference may be due to different environmental conditions in Northern Missouri compared to Ames, Iowa during seed fill/maturation. Fatty acid traits are relatively simple from a genetic perspective, and the target of ∼20% stearic acid is almost reached with three QTL from A6 (Figure 3), although we noted relatively large environmental variation (Table 2).…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…A6’s stearic acid phenotype was much lower in the three Missouri environments we studied (23.4 ± 4.4, 20.9 ± 2.9, and 22.3 ± 5.5%) as compared with the original report of 28.1% stearic acid (Hammond and Fehr 1983; Lundeen et al 1987), and this difference may be due to different environmental conditions in Northern Missouri compared to Ames, Iowa during seed fill/maturation. Fatty acid traits are relatively simple from a genetic perspective, and the target of ∼20% stearic acid is almost reached with three QTL from A6 (Figure 3), although we noted relatively large environmental variation (Table 2).…”
Section: Discussioncontrasting
confidence: 69%
“…A6 bears several large genomic deletions, including a large portion of chromosome 14 (∼6,221,000 bp) corresponding to ∼1/8 of the chromosome (Gillman et al 2014). Regrettably, A6 is also extremely agronomically deficient, exhibiting poor germination, low seed yield, reduced seed quality, extreme early maturity (MG 0), and short plant stature when alleles for elevated stearic acid are present (Lundeen et al 1987; Hammond and Fehr 1983). Some of the defects are likely due to one (or more) of the significant genomic deletions (Gillman et al 2014).…”
mentioning
confidence: 99%
“…They concluded that the agronomic performance of reduced linolenate lines is not associated with genetic changes related to mutation for reduced linolenate content. Lundeen et al (1987) reported that an allele controlling elevated stearate content in soybean oil was associated with agronomic performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another property of these alleles in Arabidopsis is to cause up to a 5-fold reduction in plant size. Interestingly, fas a , fas b , and fas alleles also severely depressed yield in soybean (Lundeen et al 1987;Hartman et al 1997). This decrease in yield may be one of the reasons for the slow progress in the development of acceptable commercial cultivars with higher stearic acid content.…”
Section: Introductionmentioning
confidence: 99%